2022
DOI: 10.1088/1748-9326/ac9b50
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing the evidence of nitrous oxide mitigation practices in agroecosystems

Abstract: Nitrous oxide (N2O) emissions from agricultural soils are the main source of atmospheric N2O, a potent greenhouse gas, and key ozone-depleting substance. Several agricultural practices with potential to mitigate N2O emissions have been tested worldwide. However, to guide policymaking for reducing N2O emissions from agricultural soils, it is necessary to better understand the overall performance and variability of mitigation practices and identify those requiring further investigation. We performed a systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 120 publications
1
11
1
Order By: Relevance
“…In 44 site‐years of measurements on the Canadian Prairies, the use of such double inhibitors reduced emissions by 40% (M. Tenuta, personal communication), even without counting the rate adjustments possible from reduced total losses and higher N use efficiency with these products. This reduction figure roughly agrees with a recent global “meta‐analysis of meta‐analyses” (Grados et al., 2022), which found an average reduction of 49% for the same comparison. The use of a nitrification inhibitor on its own produces a similar reduction, but caution is encouraged when applied to urea because of the risk of increasing ammonia volatilization in some situations (Fan et al., 2022).…”
Section: Canadasupporting
confidence: 90%
See 1 more Smart Citation
“…In 44 site‐years of measurements on the Canadian Prairies, the use of such double inhibitors reduced emissions by 40% (M. Tenuta, personal communication), even without counting the rate adjustments possible from reduced total losses and higher N use efficiency with these products. This reduction figure roughly agrees with a recent global “meta‐analysis of meta‐analyses” (Grados et al., 2022), which found an average reduction of 49% for the same comparison. The use of a nitrification inhibitor on its own produces a similar reduction, but caution is encouraged when applied to urea because of the risk of increasing ammonia volatilization in some situations (Fan et al., 2022).…”
Section: Canadasupporting
confidence: 90%
“…The use of a nitrification inhibitor on its own produces a similar reduction, but caution is encouraged when applied to urea because of the risk of increasing ammonia volatilization in some situations (Fan et al., 2022). For slow‐ and controlled‐release fertilizers, the reduction found was 33%, and for urease inhibitors, 23% (Grados et al., 2022). Thus, clearly it is possible through choices of “right source” to substantially mitigate nitrous oxide emissions, providing large value in the effort to move society to “net zero” in terms of emissions that affect the climate.…”
Section: Canadamentioning
confidence: 99%
“…Biochar enhanced crop yield, reduced N 2 O and NH 3 emissions, but increased CO 2 emissions. Grados et al [35] conducted a systematic review to assess the N 2 O emission mitigation practices in agricultural soils using 27 meta-analyses from 1119 primary studies and found that technology-driven solutions such as enhanced-efficiency fertilizers, drip irrigation, and biochar and optimization of fertilizer rate have considerable mitigation potential. Agroecological mitigation practices such as organic fertilizer and reduced tillage may enhance N 2 O emissions.…”
Section: Mega-analysismentioning
confidence: 99%
“…(Christianson et al, 2018;IEPA et al, 2015; Iowa impacts such as increased N 2 O emissions. Several synthesis studies have documented higher N 2 O emissions with cover crops as a potential tradeoff, up to 37% in a recent secondorder meta-analysis (Basche et al, 2014;Grados et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Given the lack of studies evaluating multiple N loss pathways in the same site‐year (Eagle et al., 2017), it remains unknown whether efforts to reduce NO 3 ‐N losses will have unintended environmental impacts such as increased N 2 O emissions. Several synthesis studies have documented higher N 2 O emissions with cover crops as a potential tradeoff, up to 37% in a recent second‐order meta‐analysis (Basche et al., 2014; Grados et al., 2022).…”
Section: Introductionmentioning
confidence: 99%